Literature Review on the Quizizz Platform as a Mathematics Learning Media at the Middle School/Equivalent Level in Indonesia - Ayumi, Nadia Meidina (JMEA : Journal of Mathematics Education and Application, 2024)
This research is literature research using the Systemic Literature Review or SLR research method. The background to this research problem is that mathematics is a science that is studied at all levels of education, but students' mathematics learning outcomes in Indonesia are quite low, because mathematics is still considered a difficult or boring subject. Many researchers use technology-based mathematics learning media using the Quizizz platform to improve learning outcomes. Quizizz platform users from Indonesia rank second highest in the world in June 2024. Therefore, the aim of this research is to determine the causes of the popularity of Quizizz use in Indonesia, especially at the secondary school level. Through analysis of the results and discussion, it was found that the popularity of the Quizizz platform at the secondary school level in Indonesia was caused by two main factors, such as (1) ease of use and (2) benefits of use. Ease of use includes mobile friendly access, varied and interesting features, as well as a usage guide. Meanwhile, the benefits of using it include increasing students' knowledge aspects (such as problem solving abilities) and skills aspects (such as the ability to apply technology), motivation, etc. Apart from that, this application is also useful for educators in terms of time efficiency, both in terms of creating learning tools and evaluation.